2019
DOI: 10.35762/aer.2019.41.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of Distribution and Quantity of Plastic-debris on Beaches Along the Coast at Phuket Province

Abstract: The beach sediment samples from Kalim, Tri Trang, and Patong Beaches, Phuket Province, southern of Thailand were collected for preliminary investigation on coastal debris. A total of 9 samples were taken from a 1 x 1 m quadrat at the depth of 5 cm, parallel with the shore during the period of maximum low tides in November, 2018. Microplastics (particles size < 5 mm) were extracted using sodium chloride (1.15 g mL-1) and their characteristics- including abundance (ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 16 publications
(30 reference statements)
2
6
1
Order By: Relevance
“…In addition, the tidal ocean currents and winds can contribute greatly to the migration, distribution and concentration of microplastics in the ocean, with deposition affected by intertidal effects. Notably, the microplastic abundance in beach sediments found in this study area was definitely higher than at other sites investigated previously along the west coast of Phuket [5,13]. Akkajit, et al [5] found microplastic at the most popular beaches of Patong, Kalim, and Tri Trang, ranging from 22.8 to 82.2 items kg −1 d.w. for >300 μm and from 22.9 to 69.7 items kg −1 d.w. for the size range of 20 to 300 μm.…”
Section: Abundances Of Microplastics In Beach Sediment At Mai Khao Beachcontrasting
confidence: 52%
See 1 more Smart Citation
“…In addition, the tidal ocean currents and winds can contribute greatly to the migration, distribution and concentration of microplastics in the ocean, with deposition affected by intertidal effects. Notably, the microplastic abundance in beach sediments found in this study area was definitely higher than at other sites investigated previously along the west coast of Phuket [5,13]. Akkajit, et al [5] found microplastic at the most popular beaches of Patong, Kalim, and Tri Trang, ranging from 22.8 to 82.2 items kg −1 d.w. for >300 μm and from 22.9 to 69.7 items kg −1 d.w. for the size range of 20 to 300 μm.…”
Section: Abundances Of Microplastics In Beach Sediment At Mai Khao Beachcontrasting
confidence: 52%
“…It is clean and natural, and is one of the few Phuket beaches where nesting sea turtles can be found using it as a breeding ground [12]. Recent studies have reported on the occurrence and distribution of microplastics in beach sediments in Phuket [5,13,14] but still little is known about the distribution of microplastics along the Mai Khao coastline. Much of the plastics used in the tourism industry contribute to plastic waste, especially in coastal areas.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have focused on heavy metal accumulation in the sediment and in marine bivalves (Marcia optima) species collected from the coastal area of Phuket Bay [18][19]. Most studies on microplastics contamination at Phuket have focused on the beach sediment, usually by tourist attractions [20][21]; however, there is limited literature available on microplastics contamination in marine organisms, especially in the marine bivalve Perna viridis that is an ecologically and commercially common marine bivalve species consumed by humans. In Phuket, the green mussel Perna viridis is considered one of the major aquaculture species, and it is the most consumed commercial species of bivalves in the fishery markets.…”
Section: Introductionmentioning
confidence: 99%
“…MP contamination was found in beach samples and invertebrates on the east coast of Thailand where there are recreational areas (Bissen and Chawchai, 2020; Thushari et al, 2017). Furthermore, a large amount of MPs was detected at a very popular beach in Phuket (Akkajit et al, 2019). Most MP samples are probably derived from the fragmentation of fishing equipment or wastewater effluent (Akkajit et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a large amount of MPs was detected at a very popular beach in Phuket (Akkajit et al, 2019). Most MP samples are probably derived from the fragmentation of fishing equipment or wastewater effluent (Akkajit et al, 2019).…”
Section: Introductionmentioning
confidence: 99%